PENGEMBANGAN PEMBELAJARAN LEMPAR LEMBING MENGGUNAKAN MEDIA ROKET PADA SISWA KELAS IX SMP N 2 PEMALANG TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The aim of this research is find the media learning that suitable for the student of IX class in SMP N 2Pemalang. The method of research is the research and development method from Suharsimi Arikunto. Thedata collection process done by using the questioner that arrange by the evaluator expert, student questioner, thesmall group experiment, and the field experiment. The data analysis technique that used is descriptivepercentage to discover the psychomotor aspect, cognitive aspect , and affective aspect of student. The data thatfound are, evaluating the expert of Penjas 92% (very good), valuating the learning expert 98% (very good),from this wide scale experiment we got the result of questioner with average selection answer percentage is 90%(very good). The result of cognitive learning of students are 88%. From those data , we can say that the ball tailmedia development effective for the student of IX F class SMP N 2 Pemalang.